Chronic Extradural Hematomas: An Illustrative Case Report and Review of Literature - Rajeev Sharma; Satish Kumar Verma; Sumit Sinha (Indian Journal of Neurosurgery)
With the easy availability of computed tomography scanning, the majority of large extradural hematomas are identified and evacuated early. Hence, a large chronic extradural hematoma (CEDH) is rarely encountered in current clinical practice. The authors describe an interesting case of a large bifrontal CEDH associated with superior sagittal sinus injury in a 32-year-old man. We also present a review of 43 cases available in the literature, and discuss various concepts of classification of CEDHs and their management.